The Correlation between Frequency of Use and Students’ Long Term Memory of Words Meanings and Usages at SMP N 5 Singaraja in Academic Year 2013/2014 - ., Ni Kadek Swadnyani; ., Prof. Dr. Dewa Komang Tantra,Dip.,App.; ., Luh Diah Surya Adnyani, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
dan frekwensi penggunaan makna dan penggunaan kata. Tiga masalah yang dibahas dalam penelitian ini adalah tentang jumlah makna dan penggunaan kata yang siswa ingat, frekwensi siswa menggunakan makna dan penggunaan kata di dalam empat keterampilan berbahasa, dan hubungan antara memori dan frekwensi penggunaan makna dan penggunaan kata. Penelitian ini dilaksanakan di SMP N 5 Singaraja dan sampel yang digunakan adalah siswa kelas tujuh yang terdiri atas 62 siswa. Data dikumpulkan dengan menggunakan tes dan kuesioner. Hasil tes menunjukkan bahwa jumlah makna dan penggunaan kata yang mampu diingat oleh siswa adalah paling banyak 115 kata (90%) dari jumlah total kata yaitu 128 kata. Sementara jumlah makna dan penggunaan kata yang paling sedikit diingat oleh siswa adalah 64 kata (50%). Kelas kata yang paling banyak siswa ingat tentang makna dan penggunaan kata adalah noun yaitu sebanyak 75% dan kelas kata yang paling sedikit diingat oleh siswa yaitu adverb sebanyak 42%. Hasil kuesioner menunjukkan bahwa siswa mempergunakan makna dan penggunaan kata paling sering di dalam keterampilan membaca yaitu 62 siswa (100%) dan siswa tersebut sering menggunakan makna dan penggunaan kata dalam hal kelas kata yaitu noun, verb, adjective, and adverb di dalam keterampilan yang sama yaitu membaca. Hasil analisis data menunjukkan bahwa terdapat suatu hubungan yang positif antara memori dan frekwensi penggunaan makna dan penggunaan kata. Hal ini dibuktikan dengan melihat Point-Biserial Correlation koefisien r yaitu 0.564. Kata Kunci : memori, frekwensi penggunaan makna dan penggunaan kata The objective of this research was to know whether there is any correlation between memory and uses of the words meanings and usages. There are there research problems were examined. It is about the total words meanings and usages remembered by the students, the uses of the words meanings and usages in the four language skills, and the correlation between memory and uses of the words meanings and usages. This research conducted at SMP N 5 Singaraja and the sample used was students in the seven grade consisted of 62 students. The data were collected using test and questionnaire. The result of test shows that the highest total number of words meanings and usages remembered by the students is 115 words (90%) from the total number of words is 128 words while the lowest total number of words meanings and usages remembered by the students is 64 words (50%). The most word class remembered by students in terms of word meanings and usages is noun that is 75% and word class adverb is 42% remembered by the students. The result of questionnaire shows that students used words meanings and usages frequently in reading. In reading, 62 students (100%) used words meanings and usages in terms of word class noun, verb, adjective, and adverb. The result of data analysis shows that there is a significant correlation between memory and uses of words meanings and usages. It could be seen by looking at the result of Point-Biserial Correlation coefficient r that is 0.564.keyword : memory, uses of words meanings and usages